2020
DOI: 10.1007/s40430-020-02446-8
|View full text |Cite
|
Sign up to set email alerts
|

Nano-fluid lubrication of single-layered porous hydrostatic bearing: a theoretical approach

Abstract: A theoretical framework of single-layered PHB (porous hydrostatic bearing) lubricated by nano-oil has been developed here. The impact of nano-oil on the presentation of said hydrostatic bearing has been concentrated with the assistance of modified Darcy's law and distinctive boundary conditions. The different nanoparticles are utilized as an added substance of conventional lubricants to upgrade its consistency. The statement of dimensionless exhibition attributes of the researched bearing has been determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…The results show that when using contrast nanolubricants and equivalent other Newtonian fluids and micropolar fluids, the exposure quality is significantly improved. 40,[62][63][64][65] The dispersion of CuO nanoparticles in three biolubricants is used to study the frictional performance and pressure distribution of nano-bio-lubricants, biolubricants, and ISO VG46 oil. The pressure distribution profiles are the same regardless of the type of oil at all speeds and loads.…”
Section: Types Of Nanofluid Additives Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that when using contrast nanolubricants and equivalent other Newtonian fluids and micropolar fluids, the exposure quality is significantly improved. 40,[62][63][64][65] The dispersion of CuO nanoparticles in three biolubricants is used to study the frictional performance and pressure distribution of nano-bio-lubricants, biolubricants, and ISO VG46 oil. The pressure distribution profiles are the same regardless of the type of oil at all speeds and loads.…”
Section: Types Of Nanofluid Additives Examplesmentioning
confidence: 99%
“…The results show that when using contrast nanolubricants and equivalent other Newtonian fluids and micropolar fluids, the exposure quality is significantly improved. 40,6265…”
Section: Nanoparticles Added Lubricantsmentioning
confidence: 99%
“…Thermal and elastic effects on the performance of 170°p artial bearing were presented by Shamal et al 17 They discussed the circumferential effect of scratches on the static and thermal parameters. Non-Newtonian behavior of lubricant was studied by References [18][19][20] with couple stress fluid, [21][22][23] with nano-fluid. They showed an improvement in the performance of partial bearing as compared with Newtonian fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Suryawanshi and Pattiwar (2018) compare the performance of plain and elliptical journal bearing with the addition of nanoparticles by measuring the shear viscosity at various weight concentrations of nanoparticles by using Tribo tester and found the improvement in the performance of the elliptical bearing over the plain shaped bearing. Bhattacharjee et al (2020) studied the effect of nanoparticles–oil on hydrostatic bearing by using modified Darcy’s flow model and found that the performance is improved with the addition of nanoparticles in the lubricant. Sadabadi and Sanati Nezhad (2020) studied the performance of IF-WS2 nanofluid lubricant in bearing by using computational approach with discrete modeling, and the results showed the improvement in LCC.…”
Section: Introductionmentioning
confidence: 99%